Exploratory Data Analysis of Agricultural Commodity Prices Across Districts and Cities in East Java - Tamam, Moh. Badri; Araujo Bernardo, Januario Freitas (Intelmatics, 2026)
Descriptive statistics and visualization revealed significant variations in price distributions, with medium rice, premium rice, and dry milled paddy being the predominant commodities. Monthly trend analysis indicated a consistent upward movement in prices from 2020 to mid-2025. Regional comparisons specifically highlighted that, among all districts studied, Bondowoso had the highest average rice prices, Magetan consistently showed the lowest prices, and Malang City exhibited the greatest price volatility. The Random Forest Classifier achieved 73% accuracy in distinguishing districts based on commodity price patterns. Feature importance analysis singled out medium rice and premium rice as the most influential variables driving classification. These key findings clarify the specific pricing trends, regional disparities, and significant predictors identified in the study.